MEGALITHIC CULTURE IN RAJEKWESI VILLAGE KENDIT DISTRICT SITUBONDO REGENCY - Afif, Muarafa Nur; Swastika, Kayan; Sumarjono, Sumarjono; Naim, Mohamad; Pratama, Akhmad Ryan; Jamil, Robit Nurul (History Education, University of Jember, 2022)
The purpose of this study is to take an inventory of the number of archaeological remains of megalithic culture and other archaeological. The results of this study are the number of archaeological remains of megalithic culture at the Rajekwesi site, with locations spread over two hamlets, namely West Tobe Hamlet 4 remains and East Tobe Hamlet as many as 19 megalithic remains. close together. The belief system, social, economy, and culture adopted by the megalithic cultural community of the Rajekwesi Site, They also have a fairly complex order, namely the existence of social differentiation and social stratification, the culture of the megalithic community at the Rajekwesi Site is confirmed to have an egalitarian or mutual cooperation pattern.